2021
DOI: 10.3389/fbioe.2021.782224
|View full text |Cite
|
Sign up to set email alerts
|

PuraStat RADA16 Self-Assembling Peptide Reduces Postoperative Abdominal Adhesion Formation in a Rabbit Cecal Sidewall Injury Model

Abstract: Objective: To evaluate the effect of PuraStat (2.5% RADA16) administration on postoperative abdominal adhesion formation in an in vivo model.Methods: Anesthetized New Zealand white rabbits underwent cecal sidewall abrasion surgery in which the cecal serosa and juxtaposed parietal peritoneum were abraded after access through an abdominal midline incision. Eight animals were randomized to receive PuraStat administration at the interface of the injured tissues before incision closure, and five animals served as u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…RADA16 functions as a topical hemostatic agent for surgery and prevents adhesion formation after surgery. [65] Previously the Hartgerink group studied diabetic wound healing in mice with SAPH composed of self-assembling domain without the biological mimics with significantly accelerated wound closure in their SAPH, K2, compared to a commercially available hydrogel, IntraSite, and buffer groups. [57] SAPHs, including RADA16 and K2, can be modified with various functional peptides to develop bioactive SAPHs imbued with the abilities of the appended mimetic sequence.…”
Section: Discussionmentioning
confidence: 99%
“…RADA16 functions as a topical hemostatic agent for surgery and prevents adhesion formation after surgery. [65] Previously the Hartgerink group studied diabetic wound healing in mice with SAPH composed of self-assembling domain without the biological mimics with significantly accelerated wound closure in their SAPH, K2, compared to a commercially available hydrogel, IntraSite, and buffer groups. [57] SAPHs, including RADA16 and K2, can be modified with various functional peptides to develop bioactive SAPHs imbued with the abilities of the appended mimetic sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Eun Seok Gil and co‐workers conducted one cecal sidewall abrasion surgery to evaluate post‐operative abdominal adhesion formation in rabbit animal model. [ 274 ] 2.5% RADA16 peptide formulation might achieve 79% higher mean mucosal coverage area in cecal sidewall wound sites in RADA16 peptide‐treated group than control ( p < 0.001). For the post‐operative management of peritoneal effusion in pelvic surgery, RADA16 peptide hydrogel exhibited effective hemostasis and safe tissue‐sealing quality superior to other topical hemostatic materials such as collagenous materials and fibrin glue.…”
Section: Clinical or Preclinical Use Of Dsap Biomaterials In Surgical...mentioning
confidence: 99%
“…We next assessed whether barrier material alone (e.g., hydrogel) is sufficient to prevent inflammatory/fibrotic processes during PA since SAP hydrogel (RADA16) has been shown to reduce PA to some extent. [10,12] KLD12 (n-KLDLKLDLKLDL-c) is an ionic-complementary SAP peptide containing altered positively charged lysines and negatively charged aspartic acids, and its net charge is zero. [25] To obtain a cationic SAP peptide, we added two arginines at the C-terminus of KLD12 (n-KLDLKLDLKLDLRR-c, KLD2R) as previously reported.…”
Section: Sap Hydrogel Alone As a Barrier Materials To Partially Atten...mentioning
confidence: 99%
“…In fact, a pilot study showed some positive effects of RADA16 hydrogel in preventing adhesion formation in a rabbit cecal sidewall injury model. [ 12 ] However, the beneficial roles of SAP hydrogel alone in preventing PA may be mainly due to its cross‐linked nanofiber structure that can cover injured sites, since its direct anti‐inflammatory or antifibrotic role is rarely reported. Thus, the biofunctions of SAP may be specifically improved by integration with bioactive components.…”
Section: Introductionmentioning
confidence: 99%